Systematic review of the use of endo-luminal topical negative pressure in oesophageal leaks and perforations. Issue 3 (2nd March 2017) - Newton, N. J.; Sharrock, A.; Rickard, R.; Mughal, M.
SUMMARY: Topical negative pressure is widely used in the management of superficial wounds. The use of this technology in the management of oesophageal perforations is becoming increasingly common. This systematic review aims to capture available evidence about its use in this setting. Medline and Embase were searched using MeSH terms and free text: esophageal perforation; esophageal injury; vacuum assisted closure; vacuum therapy device; esophagus; wounds penetrating; esophageal perforation; wound healing; negative pressure wound therapy. Searches were carried out between April and November 2015. Case series, cohort trials and controlled trials were included. Additional studies were found by hand searching reference lists. Eleven studies met the inclusion criteria with 180 patients. Nine of the studies were case series and two were retrospective comparisons of negative pressure with stents or clips. Healing of the perforation occurred in 163/179 patients and the overall mortality was 12.8%. Compared with published data on mortality from oesophageal perforation, the application of negative pressure appears to be beneficial. The studies are, however, limited to case series and retrospective cohort studies. The number of patients in each study is small and in the absence of randomized trials demonstrating a lack of bias firm conclusions cannot be made.